Listening to China’s Cultural Revolution: Music, Politics, and Cultural Continuities - Clark, Paul; Pang, Laikwan; Tsai, Tsan-Huang (Chinese Literature and Culture in the World, 2016)
Bringing together the most recent research on the Cultural Revolution in China, musicologists, historians, literary scholars, and others discuss the music and its political implications. Combined, these chapters, paint a vibrant picture of the long-lasting impact that the musical revolution had on ordinary citizens, as well as political leaders.